Active labour market policies in the European Union. - Mathiesen, Külli (2012)
Introduction Employment has been one of the most important topics in Europe´s history over times. The goal to achieve full employment is desirable for every country in the European Union, but it is more than clear that this goal is unreachable. It is impossible to get full employment and people have accepted the fact that there will always be unemployed people. Politicians and scientists usually say that an unemployment rate which would not cause a significant damage to the whole country would be a rate of around 5% from working -aged population. Nowadays, after the economical crisis in Europe, the unemployment rate has grown much more than 5% in most of the countries. How to save Europeans from poverty and social exclusion? How to save countries from bankruptcy on the one hand and, on the other hand, still manage to keep them as welfare states? These are the questions which several citizens and politicians have been asking themselves. To improve the labour market and achieve a higher employment rate, the European (...).